Comparison of Total Phenolic Content and Antioxidant Activity of Indonesian Propolis Extracted with Various Solvents. - Diah Kartika Pratami; Nur Elistiani Eksadita; Muhamad Sahlan; Abdul Mun’im; Asep Bayu; Kaysa Faradis Mahira (Fakultas Farmasi Universitas Pancasila, 2023)
Propolis is a widely used medicine that may be found in both its pure form and when combined with othernatural ingredients in over-the-counter preparations, cosmetics, and health foods. Some customers develop alcohol sensitivity after using ethanol, which is a common solvent to extract propolis. As propolis solvents, various Natural Deep Eutectic Solvents (NaDES) were examined in this study. Choline chloride, propylene glycol, glycerol, citric acid, and 1,2-propanediol were combined in molar ratios to create some of the NaDES that were employed. Propolis and solvents were used in a kinetic maceration ratio for the extraction process. The Folin-Ciocalteu method was used to measure the total phenolic content (TPC), and the DPPH assay was used to measure antioxidant activity. In ethanol and NaDES solvents, the TPC of propolis extract ranged from 136.52 ± 27.9 to 365.8 ± 20.54 mgGAE/g. The values for antioxidant activity were 45.94 to 183.76 ppm. The propolis extract with the lowest IC50 and the highest TPC content was choline chloride-glycerol (CCG). It was discovered that the optimum NaDES solvent for extracting propolis was CCG-based. NaDES may be a potential solvent for use in Indonesian propolis, both as an extraction medium and as a formulation element.